Peran Wakaf Produktif dalam Pemberdayaan Ekonomi - Bakhri, Amirul; fariyati, Sri (Madaniyah, 2017)
One of the forms of worship to draw closer to Allah SWT related to property is donated. waqf istismari also called productive waqf, waqf property that is used for investment purposes, whether in agriculture, industry, trade, and services. This endowment is growing problems in the village Longkeyang, where the youth of Longkeyang attempted endowment for the welfare of citizens. In 2006, approximately 10 people from the youth of the Longkeyang together activists AMM (Angkatan Muda Muhammadiyah) began a new initiative is to create a new institution that was later (in 2010) was named after the Badan Pekerja Pengembangan Ranting Muhammadiyah (BP2RM). (1) The first step movement endowment productive Muhammadiyah Youth in Longkeyang namely (a) Establish Badan Pekerja Pengembangan Ranting Muhammadiyah (BP2RM) Longkeyang village. (a) Movement Endowments Endowments coins For Productive. (2) Management of communal ownership of productive Youth in Longkeyang namely (a) inisiation the collected coins donated as initial capital. (b) The existing endowments worked together to reduce the cost of key crops albasia timber, then the cost of treatment using the results of intercropping banana plants. (3) The Role of Waqf Productive Youth Welfare Citizens for The Longkeyang of waqf endowments suppl shroud support fund for volunteers who want to stay.